THE EFFECT OF CHAIN DRILL TECHNIQUE ON STUDENTSâ€™ SPEAKING ACHIEVEMENT AT SMP NEGERI 3 RAHA - Shyerlin, Wa Ode (Journal of Teaching of English, 2019)
This study aims to find out whether there is a significant effect of chain drill technique on the first year of SMP Negeri 3 Raha. The research question formulated â€œis there any significant effect of chain drill technique on studentsâ€™ speaking achievement at SMP Negeri 3 Raha?â€. The design of study was pre-experimental research design that consisted of one group pre-test and post-test. The population of this study was all students on the first year of SMP Negeri 3 Raha who were registered in academic year 2017/2018. The sample of this study was one class namely VII3 Â which consisted of 22 students. The instrument of this study was oral test in dialogue based on the cue card about how to greet and respond. The research used Paired Sample T- test to analyze the result of the study of the effect of chain drill technique on studentsâ€™ speaking achievement after analyzing the normality of the data in the experimental class. The result shows that studentsâ€™ speaking ability in the post test is 2.806 higher than 1.647 is the post test. The hypothesis testing is found that the level of significant is 0.00, since the level of significance value is less than 0.05, i.e. 0.00<0.05, the null hypothesis (H0) is rejected and H1 is accepted. It means that the use of chain drill technique shows a significant difference on studentsâ€™ speaking achievement on the first year of SMP Negeri 3 Raha based on the result of the post-test.Â Keywords: Speaking, Teaching Speaking, Chain Drill Technique